Character Education Through Scouting Extracurricular Activities at Nurussalam Islamic High School - Siti Winu Wulan; Iqbal Amar Muzaki; Muchdjabir Wahid (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The purpose of this study is to examine how extracurricular scouting activities at Nurussalam Jayakerta Islamic High School contribute to student character development. This research is driven by the importance of character education in the digital era, which is characterized by the moral degradation of the younger generation as a result of social media and technology. Because scouting activities combine the principles of discipline, responsibility, cooperation, leadership, and nationalism through the implementation of Tri Satya and Dasa Dharma, this activity is considered an effective medium for character education. This study used a qualitative descriptive methodology and collected data through observation, documentation, and interviews. Teachers, students actively participating in scouting activities, and scout leaders were the subjects of the study. According to the research findings, the extracurricular scouting program at Nurussalam Islamic High School serves as a primary tool for overall student character development, in addition to providing extracurricular activities outside the classroom. The character values instilled include religiosity, discipline, accountability, teamwork, leadership, nationalism, and self-control. Adequate facilities, an integrated Islamic boarding school system, and proactive support from the school and its advisors all contributed to the success of this initiative. The school was able to overcome a number of obstacles, including student boredom and a lack of extracurricular activities, by implementing unique and creative programs. Thus, in a contemporary Islamic boarding school setting, scouting activities have proven to be an excellent model for character education.